Palacios Briones,Henry Adrián(2023)EFECTO DEL INHIBIDOR DE SÍNTESIS DE GIBERELINA PACLOBUTRAZOL SOBRE EL RENDIMIENTO DEL CULTIVO DE MAÍZ (Zea mays L.) DURANTE LA ÉPOCA DE SECANO.Quevedo.UTEQ.78p. - Palacios Briones, Henry Adrián (2023)
The present investigation was carried out in the properties of the Campus "La María" of the UTEQ, where two hybrids and a Criolla variety were established, with and without the application of Paclobutrazol, the objective of the present study was to determine the effect of paclobutrazol on the yield of the maize crop during the dry season where 24 experimental units divided for six treatments were implanted applying a DCA with factorial arrangement; Factor A: Emblema, Splendor and Criolla varieties; Factor B: With and Without PBZ and an interaction: (T1 SPLENDOR witness), (T2 SPLENDOR, PBZ), (T3 EMBLEMA Witness), (T4 EMBLEMA, PBZ), (T5 CRIOLLA Witness) and (T6 CRIOLLA, PBZ). The results in plant height showed a statistical difference between the treatments, being (T6 CRIOLLA with PBZ) the one that had plants with heights of 265.59 cm at 60 DDE, unlike (T2 SPLENDOR with PBZ) which had plants with lower heights. There were no statistical differences in stem diameter, but the treatments with PBZ were thicker (T4 EMBLEM with PBZ) had an average of 2.66 cm in diameter. In the days of flowering they showed statistical difference, in treatments with PBZ it was evidenced that the flowering day of T1 and T2 SPLENDOR was extended with 65 days DDE, unlike T6 Varieties Criolla with 59.75 DDE the inhibitor. The plants with the highest yield were (T3 EMBLEMA Witness) those with 19918.50 kg/ha, unlike (T6 CRIOLLA with PBZ) which had a lower yield, concluding that PBZ is effective in varieties such as SPLENDOR and CRIOLLA which helps to improve the physiology of the plant, in Hybrids such as the EMBLEM causing limitations and therefore reduced performance.